Soil Aggregation and Aggregate Associated Carbon in a Vertisol under Conventional, Organic and Biodynamic Agriculture in Semi-Arid Tropics of Central India - and Swami Kaleshananda, Satish Bhagwatrao Aher*, Brij Lal Lakaria, Amar Bahadur Singh (Journal of the Indian Society of Soil Science, 2019)
A field experiment was conducted at Indian Institute of Soil Science, Bhopal on a clayey soil (Typic Haplusterts) under soybean (Glycine max) - wheat (Triticum durum) cropping system to study the changes in soil physical properties under organic, biodynamic and conventional agriculture. The results revealed that application of organic manures either alone or in combination with liquid organic formulations increased soil organic carbon (13-16%), yield (9-13%), MWD (20-21%) and GMD (11-12%) over inorganic fertilizer addition (RDF). The content of organic carbon in different size water stable aggregates was found higher under the organic nutrition. The treatments receiving organic manure showed 5-9, 5-8 and 4-6 per cent lower bulk density in 0-7.5, 7.5-15.0 and 0-30 cm soil depths, respectively over RDF. No significant difference was observed under biodynamic agriculture.